Classifying Façade Colors in Residential Buildings Based on Color-Emotional Scales - Maryam Mehdipour; Ahmad Ekhlasi; Seyed Abbas Yazdanfar (منظر, 2023)
The lack of facade color control programs in urban planning policies in Iran and the choice of facade color based on the designer’s taste make it necessary to design façade colors based on scientific principles and users’ evaluations. In color studies, emotional scales have been used to describe color. Due to the relative nature of emotional terms and the lack of consensus on definitions of these scales under the influence of contextual factors and individual characteristics of users, there is a need to redefine these scales in the context of Iran.This study aims to identify and determine the scales and components to classify the color combination of the façade. For this purpose, a combination of qualitative and quantitative methods was used. Twenty experts in the field of design and color participated in the Delphi survey, and the data were analyzed using the Q method. The finding presented three bipolar scales: temperature, harmony, and weight, to classify the facade color combination. In the next step, through semi-structured interviews with five architects and urban planners, components were determined to describe these three scales. Then, the authors of the study prepared a questionnaire to confirm the components completed by 20 former experts. Components affecting three scales and selected photos of each scale were extracted by analyzing data using the Q method in two steps. The quantitative values were collected through the color strip and HSL system codes of the final photos based on the percentage of color area in the façade, the number of hues, and their temperature, lightness, and saturation. Based on the results, the façade color combinations can be classified into eight treatments: cool-harmonious-light, cool-harmonious-heavy, cool-contrasting-light, cool-contrasting-heavy, warm-harmonious-light, warm-harmonious-heavy, warm-contrasting-light, and warm-contrasting-heavy, each of which can be defined using quantitative values.